UPAYA GURU DALAM MENGHADAPI IMPLEMENTASI KURIKULUM MERDEKA DI KELAS IV SDN MERJOSARI 3 KOTA MALANG - Chusnul Chotimah; Kardiana Metha Rozhana; Alfonsia Anu Betekeneng (Jurnal Cakrawala Ilmiah, 2023)
The general objective of this study is to describe the efforts of grade IV teachers in dealing with the implementation of the independent curriculum. The benefit of this research is that it becomes a reference for other class teachers before implementing the independent curriculum in their classes. The research method used is a qualitative research method with a descriptive approach. The research subjects were class IV teachers and principals of SDN Merjosari 3 Malang City. Techniques in collecting data using interview techniques, observation, and documentation. Data analysis techniques use the theory of Milles and Huberman which starts with data collection, data reduction, data presentation, and conclusion. The results of this study indicate that grade IV teachers are ready to implement the independent curriculum by following various stages as an effort to deal with the implementation of the independent curriculum. Efforts made by grade IV teachers in dealing with the implementation of the independent curriculum are by finding out information personally in the news, asking questions or sharing with colleagues and participating in online and offline training. The obstacles faced were the unavailability of student books for the Pancasila Education subject and there was still some material about culture, namely new material that had to be learned a lot. Obstacles encountered can be overcome by developing their own learning materials in accordance with learning outcomes. This independent curriculum policy emphasizes the potential and talents of students. So the existence of the P5 program and the learning material presented emphasizes the skills and activeness of students. Therefore, before implementation, it is necessary to make efforts so that the implementation of the independent curriculum can run smoothly. Efforts were made to personally seek information on the news, take part in training organized by K3S and the Malang City Education Office, take part in online training on the independent learning platform which can be accessed using each study account, and share with colleagues